Relevansi Nilai Religius Film Ajari Aku Islam terhadap Pendidikan Agama Islam - Muzamil, Muzamil; AR, Fathur Rohman; Hasanah, Nurul (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Islamic Religious Education (PAI) plays an important role in shaping the character and morals of students. In this modern era, mass media, including films, have become a powerful influencer in shaping society's perceptions and values. The film